Psychology of the Stock Market - Dobosz Bartłomiej (My University, 2007)
In the thesis the author analyses the influence of behavioural finance on the real-life stock market. By studying the history and developments in the field of behavioural finance, he manages to identify key factors influencing business agents’ behaviour in the economy and on stock market in particular. The second chapter deals with the investigation of phenomena related to people’s sentiments, emotions and attitudes and their actions on the market. Finally, the last chapter describes different types of market simulations with different levels of control and supervision. Typically, the simulations are used for educational and experimental purposes. For students, such a simulation is helping in gaining the experience and getting to know the workings of the stock market. For investors and researchers, it’s an opportunity to observe small samples of investors in an artificially created environment.
Psychologia inwestora giełdowego
Keywords: behavioural finance; stock market; market simulation; finance; economy